Asthma control, quality of life, and the role of patient enablement: a cross-sectional observational study - Sousa, Jaime Correia de (Prim Care Respir J, 2013)
BACKGROUND: Self-assessment of asthma and a stronger doctor-patient relationship can improve asthma outcomes. Evidence for the influence of patient enablement on quality of life and the control of asthma is lacking. AIMS: To assess asthma severity, medication use, asthma control, and patient enablement in patients with asthma treated in primary care and to study the relationship between these variables and quality of life. METHODS: A cross-sectional study was conducted in an urban clinic in northern Portugal. Data were collected from both clinical records and questionnaires from a random sample of asthma patients. The modified Patient Enablement Instrument, the Asthma Quality of Life Questionnaire, and the Asthma Control Questionnaire were used. Peak expiratory flow and forced expiratory volume in one second (FEV(1)) were measured. Receiver operating characteristic curve analysis was performed to establish cut-off values for the quality of life measurements. The associations between enablement, asthma control, and quality of life were tested using logistic regression models. RESULTS: The study sample included 180 patients. There was a strong correlation between asthma control and quality of life (r=0.81, p<0.001). A weak association between patient enablement and asthma control and quality of life was found in the logistic regression models. Poor control of asthma was associated with female gender, concomitant co-morbidities, reduced FEV(1), and increased severity of asthma. CONCLUSIONS: The weak correlation between enablement and asthma control requires further study to determine if improved enablement can improve asthma outcomes independent of gender, severity, and concomitant co-morbidities. This study confirms the strong correlation between asthma control and quality of life.